Opportunities and challenges of the digital age for the public sector (Research, Society and Development, 2022)
This study aims to analyze the opportunities and challenges of public administrations in the digital era, in order to contribute to the understanding of the new paradigm of public management. To this end, qualitative exploratory and descriptive research was conducted, with bibliographical and narrative procedures. The results indicate that the dynamics of communication and performance of the network society put pressure on public administrations to be present where citizens are - in social media - a new digital world, which provides new spaces for interaction in the public sphere. As an emerging phenomenon, the way in which each public institution has been experiencing government-citizen digital interaction has produced relevant feedback for the understanding of public management in the 21st century. It was concluded, then, that for public administrations, especially local ones, immersed in routines and bureaucratic procedures, the digital world and the new concepts of operation have arrived in slow, gradual and differentiated ways, according to the institutional environment of each institution. And, despite the strong acceptance of ICTs in the public sector, these have not yet necessarily converted into innovations in citizen participation in decision-making processes, which, in the researchers' understanding, does not generate added value to the public sector, besides hindering the development of better policies and the provision of better services.